De bibliothecariis Persone, idee, linguaggi - Guerrini, Mauro (Studi e saggi, 2017)
In the activity of the librarian, the technical dimension, essential for working with professionalism, cannot ignore or be separated from commitment, attention to civil rights and the way in which they are lived and practiced within the community to which they belong. Ensuring access to information cannot be limited to 'our' library: it must be a responsibility that concerns the territory where we live and operate, looking to our colleagues who may find themselves in a difficult situation and especially to the people who have difficulties in exercising their rights. The hope is that the transmission of registered knowledge will contribute more and more to the freedom, rights and well-being of all. Will it still take time to understand that investing in libraries means investing in democracy, economic development and the quality of life? As always, the reference framework for understanding and interpreting library problems is that of the comparison with international library traditions, starting from the European continent, as the profession of the librarian today has a theoretical framework and an operational dimension of global reach.